Low Density Lipoprotein Receptor-Related Protein-1 (LRP1) Is Involved in the Uptake of Clostridioides difficile Toxin A and Serves as an Internalizing Receptor - Schöttelndreier, Dennis; Langejürgen, Anna; Lindner, Robert; Genth, Harald (Frontiers in Cellular and Infection Microbiology, 2020)
Toxin producing Clostridioides difficile strains cause gastrointestinal infections with the large glucosylating protein toxins A (TcdA) and B (TcdB) being major virulence factors responsible for the onset of symptoms. TcdA and TcdB enter their target cells via receptor-mediated endocytosis. Inside the cell, the toxins glucosylate and thereby inactivate small GTPases of the Rho-/Ras subfamilies resulting in actin reorganization and cell death. The receptors of TcdA are still elusive, glycoprotein 96 (gp96), the low density lipoprotein receptor family (LDLR) and sulfated glycosaminoglycans (sGAGs) have most recently been suggested as receptors for TcdA. In this study, we provide evidence on rapid endocytosis of Low density lipoprotein Receptor-related Protein-1 (LRP1) into fibroblasts and Caco-2 cells by exploiting biotinylation of cell surface proteins. In contrast, gp96 was not endocytosed either in the presence or absence of TcdA. The kinetics of internalization of TfR and LRP1 were comparable in the presence and the absence of TcdA, excluding that TcdA facilitates its internalization by triggering internalization of its receptors. Exploiting fibroblasts with a genetic deletion of LRP1, TcdA was about one order of magnitude less potent in LRP1-deficient cells as compared to the corresponding control cells. In contrast, TcdB exhibited a comparable potency in LRP1-proficient and -deficient fibroblasts. These findings suggested a role of LRP1 in the cellular uptake of TcdA but not of TcdB. Correspondingly, binding of TcdA to the cell surface of LRP1-deficient fibroblasts was reduced as compared with LRP1-proficient fibroblasts. Finally, TcdA bound to LRP1 ligand binding type repeat cluster II (amino acid 786–1,165) and cluster IV (amino acid 3332-3779). In conclusion, LRP1 appears to serve as an endocytic receptor and gp96 as a non-endocytic receptor for TcdA.